Eros and Pilgrimage in Chaucer’s and Shakespeare’s Poetry - Kowalik, Barbara (Text Matters: A Journal of Literature, Theory and Culture, 2013)
The paper discusses erotic desire and the motif of going on pilgrimage in the opening of Geoffrey Chaucer’s General Prologue to The Canterbury Tales and in William Shakespeare’s sonnets. What connects most of the texts chosen for consideration in the paper is their diptych-like composition, corresponding to the dual theme of eros and pilgrimage. At the outset, I read the first eighteen lines of Chaucer’s Prologue and demonstrate how the passage attempts to balance and reconcile the eroticism underlying the description of nature at springtime with Christian devotion and the spirit of compunction. I support the view that the passage is the first wing of a diptych-like construction opening the General Prologue. The second part of the paper focuses on the motif of pilgrimage, particularly erotic pilgrimage, in Shakespeare’s sonnets. I observe that most of the sonnets that exploit the conceit of travel to the beloved form lyrical diptychs. Shakespeare reverses the medieval hierarchy of pilgrimage and desire espoused by Chaucer. Both poets explore and use to their own ends the tensions inherent in the juxtaposition of sacred and profane love. Their compositions encode deeper emotional patterns of desire: Chaucer’s narrator channels sexual drives into the route of communal national penance, whereas the Shakespearean persona employs religious sentiments in the service of private erotic infatuations.